2019
DOI: 10.4049/jimmunol.1900059
|View full text |Cite
|
Sign up to set email alerts
|

CD31 Acts as a Checkpoint Molecule and Is Modulated by FcγR-Mediated Signaling in Monocytes

Abstract: Monocytes and macrophages express FcgR that engage IgG immune complexes such as Ab-opsonized pathogens or cancer cells to destroy them by various mechanisms, including phagocytosis. FcgR-mediated phagocytosis is regulated by the concerted actions of activating FcgR and inhibitory receptors, such as FcgRIIb and SIRPa. In this study, we report that another ITIM-containing receptor, PECAM1/CD31, regulates FcgR function and is itself regulated by FcgR activation. First, quantitative RT-PCR and flow cytometry analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…However, the role of PECAM-1 in LC remains unclear ( 45 50 ). Giovanna et al found that PECAM-1 acts as a checkpoint molecule and can negatively regulate FcγR-mediated phagocytosis by monocytes and macrophages, and downregulation of PECAM-1 correlated with decreased survival of chronic lymphocytic leukemia cells ( 51 , 52 ). Virman et al found that high expression of PECAM-1 was significantly associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of PECAM-1 in LC remains unclear ( 45 50 ). Giovanna et al found that PECAM-1 acts as a checkpoint molecule and can negatively regulate FcγR-mediated phagocytosis by monocytes and macrophages, and downregulation of PECAM-1 correlated with decreased survival of chronic lymphocytic leukemia cells ( 51 , 52 ). Virman et al found that high expression of PECAM-1 was significantly associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…CD31 is mainly associated with vascular biology, participating in important processes as cell-to-cell adhesion, transmigration of monocytes and inflammation [70] , [71] . This molecule is composed of 3 structures, six extracellular domains, an intramembrane domain and a cytoplasmic tail that have two immunoreceptor tyrosine-based inhibition motifs (ITIMs) that have multiple ligand, like SHP-1 and -2, SH2 domain containing inositol phosphatase 2, PI3K, and phospholipase C-ɣ1 [72] .…”
Section: Approaches For Extending Exosomes’ Half-lifementioning
confidence: 99%
“…These data demonstrated that the activity of early decidua γδ T cells was higher in the maternal-fetal interface. Moreover, high expression of CD31, an endothelial cell adhesion molecule [47], was also detected in early decidua, which may be related to γδ T cells resident in early decidua. It is an indisputable fact that cytokines in the maternal fetal interface play an important role in the establishment and maintenance of normal pregnancy.…”
Section: Discussionmentioning
confidence: 93%